Динаміка власного обертання пилових частинок у магнітному полі - Dzlieva, E.S.; Ermolenko, M.A.; Golubev, M.S.; Ivanov, A.Yu.; Karasev, V.Yu. (Publishing house "Academperiodika", 2022)
The self-rotation of dust particles in a magnetic field up to 0.02 T is researched. The stratified glow discharge and a coaxial magneticfield are used. The dust particles are hollow glass microspheres, whose horizontal deflection is observed. The dependences of the rotation frequency and the direction of dust grains on the magnitude and the direction of a superimposed magnetic field are studied. The hysteresis effect of a particle self-rotation direction at the variation of the magnetic field intensity is examined.